Removal of C02 from Natural gas stream using Silica Membrane - Hussein, Nas Aaryu (Universiti Teknologi PETRONAS, 2009)
In this study the synthesis, characterization, and gas transport properties of silica membranes supported on porous alumina substrate in separating or removing carbon dioxide (C02) from natural gas stream (CRt) were studied. Silica membranes are prepared by dip-coating a prepared porous alumina support in a polymeric silica sol made by base-catalyzed hydrolysis and condensation of tetraethyl orthosilicate (TEOS), Si(OCHzCH3)4, in ethanol. The membranes were characterized using Scanning Electron Microscopy and the single gas permeation test. From the SEM observation, silica membrane was tightly attached to the substrate and the average thickness of the membrane was approximately 15-16 Jl!Il. The effect of dipping time during dip-coating of the porous alumina support also been studied. Longer dipping time may improve the selectivity. Total of three samples have been produced with the same silica sol gel but at different dipping time which are at 1, 2 and 3 hour. The silica membranes with 3 hour of dipping time displayed high C02 permeance (3.35963xl0~ mollm2.s.Pa) but small selectivity of 1.398 towards COz.The gas permeation test is conducted at room temperature and with different feed pressure of 1.5, 2.0, 2.5 and 3.0 bar. All synthesized silica membrane, show high permeance of C02 (COzpermeance > CRt permeance) thus give the evidence that the mechanism of molecular differentiation by silica layer is through size selectivity. However, the selectivity of these membranes is smaller compared to idea Knudsen separation factor of 1.66. This small deviation from ideal Knudsen diffusion may be due to a minute number of microcracks in the membrane layer, which were not observable by SEM, but detected by this test. (Small defects and cracks often appear in thin films during the calcinations process ).However, the selectivity of the synthesized silica membrane can be improved through some modification which is by applying multiple separation layer of silica sol on the top membrane. The formation of several separation layers will gradually decreased the pore size of the membrane leading to greater selectivity of separation gas especially C02 and CRt separation. 1